2001
DOI: 10.1006/dbio.2001.0216
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Communication via Connexin43 Gap Junctions Is Required for Ovarian Folliculogenesis in the Mouse

Abstract: The ovarian follicle in mammals is a functional syncytium, with the oocyte being coupled with the surrounding cumulus granulosa cells, and the cumulus cells being coupled with each other and with the mural granulosa cells, via gap junctions. The gap junctions coupling granulosa cells in mature follicles contain several different connexins (gap junction channel proteins), including connexins 32, 43, and 45. Connexin43 immunoreactivity can be detected from the onset of folliculogenesis just after birth and persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
233
2
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(254 citation statements)
references
References 59 publications
8
233
2
5
Order By: Relevance
“…Simon et al (1997) showed, that Cx37 deficient mice lack mature Graafian follicles and develop numerous incomplete corpora lutea. Loss of Cx43 on the other hand resulted in an arrest of follicular growth, with most follicles failing to develop multiple granulosa cell layers characteristic of secondary follicles (Ackert et al, 2001;Gittens et al, 2003). This implies that the presence of Cx37 and functional regulation and/or turnover of Cx43 are necessary for ovulation in late folliculogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Simon et al (1997) showed, that Cx37 deficient mice lack mature Graafian follicles and develop numerous incomplete corpora lutea. Loss of Cx43 on the other hand resulted in an arrest of follicular growth, with most follicles failing to develop multiple granulosa cell layers characteristic of secondary follicles (Ackert et al, 2001;Gittens et al, 2003). This implies that the presence of Cx37 and functional regulation and/or turnover of Cx43 are necessary for ovulation in late folliculogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dysmorphogenesis of the heart leading to early neonatal death (31,38), offspring lacking Cx43 exhibit pathophysiological features in a variety of organs. These include slowed cardiac conduction and increased susceptibility to arrhythmias (8,14,22), precataractogenic lesions in the lenses (12), delayed ossification and osteoblast dysfunction (21), impaired hematopoiesis (27), reduced germ cell numbers in the fetal gonads (17), and disrupted gametogenesis in both sexes (1,32). It is the latter consequence of the loss of Cx43 that is the focus of the present report.…”
mentioning
confidence: 94%
“…As follicles grow and reach maturity, the expanding granulosa cell population continues to express Cx43 (19,35). Given the presence of this connexin from the onset of folliculogenesis, it was not surprising that developing follicles arrest in preantral stages when Cx43 is absent (1). However, interpretation of this finding was complicated by the fact that granulosa cells lacking Cx43 retain the ability to form gap junctions when paired with wild-type granulosa cells in a dye preloading assay (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to justify or negate this notion, the present study was carried out to examine the developmental competence of OPU-derived COCs by studying the expression profile of a panel of genes, related to oocyte proper, cumulus-oocyte interaction, fertilization, embryonic development and apoptosis, both at germinal vesicle (GV) stage as well as after in vitro maturation (IVM). The panel of genes selected for expression analysis included genes associated with: follicular development and ovulation like, CONNEXIN37, CONNEXIN43, BMP15, GDF9, bFGF (Gospodarowicz et al, 1985;Goodenough et al, 1996;Fair et al, 1997;Simon et al, 1997;Elvin et al, 1999;Otsuka et al, 2000;Ackert et al, 2001;Nilsson et al, 2001;Granot and Dekel, 2002;Gittens et al, 2003;Moore and Shimasaki, 2005); Fertilization like, ZP2 and ZP3 (Chen et al, 2011;Shah et al, 2015); Embryonic-genome activation like, ZAR1, HSF1 (Christians et al, 2000;Wu et al, 2003); and Embryonic survival like, BAX, BID, BCL-XL, MCL1 (Chang and Yang, 2000;Jin et al, 2007;Goovartaes et al, 2011). The developmental competence was further elucidated by comparing embryonic developmental potential of Group 1 and Group 2 oocytes, following in vitro fertilization (IVF) and culture of the presumed zygotes.…”
Section: Introductionmentioning
confidence: 99%